EXTENSIVE DICKITIZATION OF THE PERMO-TRIASSIC FLUVIAL SANDSTONES FROM THE EASTERN IBERIAN RANGE, SPAIN - Martín-Martín J.D.; Gómez-Gras D.; Sanfeliu T.; Thiry M.; Ruiz-Cruz M.D.; Franco F. (My University, 2007)
Diagenetic kaolin minerals are very common in the Permo-Triassic succession from the SE Iberian Range, Spain. The morphology and crystal structure of kaolin minerals has been examined in four size fractions (<1 µm, <2 µm, <6.3 µm and <20 µm) of sandstone samples by means of scanning electron microscopy, X-ray diffraction, infrared spectroscopy, differential thermal analysis and thermogravimetry. Experimental data reveal that dickite is the dominant kaolin-type mineral in the entire range of size fractions, whereas small amounts of kaolinite coexists with dickite in all size fractions. Dickite appears typically as booklets of pseudo-hexagonal plates with blocky habit. The increase in size fraction is concomitant with the increase in the amount of dickite and the progressive improvement of its structural order. The extensive dickitization is attributed to the high paleogeothermal gradient recorded in the studied area and the increase in H+, presumably resulting from the flux of organic acids derived from the underlying Carboniferous rocks and/or the late Permian succession. These conditions are more likely to be associated with the late Cretaceous post-rift thermal stage of the eastern Iberian Basin. Lately, during the maximum burial depth, the fine crystalline kaolin minerals were slightly illitized. Given the very small feldspar content in the studied sequence, the results reflect the important contribution of mica alteration to the early diagenetic formation of kaolinite as well as the late conversion to dickite.
Keywords: CRYSTAL STRUCTURE; DIAGENESIS; DICKITE; KAOLINITE; MORPHOLOGY; PALEOGEOTHERMAL GRADIENT; PERMIAN; SANDSTONES; TRIASSIC; Paleozoic::Permian; Палеозой::Пермская; Mesozoic::Triassic; Мезозой::Триасовая